FAKTOR-FAKTOR KEJADIAN STUNTING PADA ANAK USIA 24-60 BULAN DI DESA PAKEL KECAMATAN PAKEL KABUPATEN TULUNGAGUNG - Linda Andri Mustofa Mustofa; `Dina Ainul Fadlika (STIKES dan AKZI Karya Husada Kediri, 2022)
Stunting is one of the public health problems faced by the Indonesian people. Stunting is a condition caused by inadequate nutritional intake. In Indonesia, the prevalence of stunting in children reaches 27.67%. Identification of factors related to stunting is needed to develop prevention strategies. The purpose of this study was to describe the factors of history of exclusive breastfeeding, family income, and complementary feeding for children aged 24-60 months who experienced stunting at Pakel Health Center, Pakel District, Tulungagung Regency. The research design used is descriptive, with a single variable including a history of exclusive breastfeeding, family income, and exclusive breastfeeding. The study was conducted at the Pakel Public Health Center, Tulungagung Regency from 5 to 6 July 2022. The population was all children aged 24-60 months who experienced stunting in the Pakel Community Health Center area with a total of 40 children. A sample of 40 was selected using a total sampling technique. The data collection technique used a questionnaire which was then analyzed in the form of a frequency distribution. The results showed that 24 respondents (60%) did not give exclusive breastfeeding, 29 respondents (73%) had incomes below the regional minimum wage and 28 respondents (70%) gave complementary feeding in the form of scraped fruit. Breast milk is the best nutrition for breastfeeding, giving complementary foods before 6 months with the wrong type before can have a risk for the baby to experience health problems in the form of infectious and non-infectious diseases that can cause growth disorders.